Colonized subjects and their emigration experiences. The case of Iranian students and their integration strategies in Western Europe. (23rd April 2017) - Karimi, Ahmad; Bucerius, Sandra M
Abstract: During the past decade, Iranian students made up a major immigration wave to European countries. A systematic study of their immigration situation, however, seems absent in the academic literature. In this paper, we are examining Iranian students' emigration decisions and their chosen integration strategies into their new host societies (Germany, the Netherlands, and Sweden) through the concepts of 'colonial mentality' and 'Anglo-conformity'. Based on fieldwork and qualitative interviews with Iranian students, our findings suggest that religio-cultural performances and language skills are the main strategies that Iranian students employ to associate themselves with Westerners before and after emigration. We conclude that the processes of immigration and integration begin long before emigration actually takes place and that the specific historico-political background of Iranian students plays an important role in these processes.